Portrait of Mick Dodson, 1999 - Milligan, Terry, 1941- (1999)
Photograph taken at a book launch in Canberra, 19/3/99.
Title from accession record.
Also available online
Keywords: Dodson, Michael, -- 1950- -- Portraits; Social reformers -- Australia -- Portraits; Aboriginal Australians -- Portraits; Political activists